An ultra-low complexity of 2:1 multiplexer block in QCA technology - Ali Hussien Majeed (Institute of Advanced Engineering and Science, 2021)
The limitations related to CMOS such as power consumption and parasitic capacitance lead scientists to search for new technologies. Quantum-dot cellular automata (QCA) is a CMOS alternative technology that uses charges instead of voltage level for binary representation. In QCA, many metrics are used for circuit differentiation such as delay, complexity and area. In this work, a new simple block of 2:1 QCA-Multiplexer is proposed. The proposed block is more efficient than previous designs by 0.43%, 0.53%, 50% and 0.72 in terms of area, complexity, delay and cost. QCADesigner software is used to design and verify the proposed circuit.